A mixed finite-element method for elliptic operators with Wentzell boundary condition - Bänsch, Eberhard; Gahn, Markus (IMA journal of numerical analysis, 2020)
Abstract. In this paper we introduce and analyze a mixed finite-element approach for a coupled bulk-surface problem of second order with a Wentzell boundary co
Advance access publication on 29 October 2018
Gesehen am 28.07.2020